(untitled) (Revista de História da UEG (REVHIST), 2019)
This article examines the "manifestos" or "roles of restoration" - which appeared in 1641, both in Portugal and in other European countries - with the intention of justifying the deposition of Philip IV of Habsburg and the acclamation of D. João IV Bragança, dynastic alteration occurred on December 1, 1640 by a coup d’état. The analysis focuses on the process of constructing a certain "memory of Philippine tyranny" in these “manifestos” - through a certain understanding of the character of the Iberian Union and its establishment in 1580 by the literary restorers - who emphasize the upheavals of Philip III’s IV to the Agreement of Tomar (1581), kind of inaugural document of the said Union of the Crowns. The period between 1580 and 1640 will then emerge as "memory years", practically demonized in Lusitanian history from the Restoration.